2016
DOI: 10.1136/ejhpharm-2015-000733
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antibiotic self-medication practice among public in the northwestern region of Pakistan

Abstract: BackgroundSelf-medication with antibiotics is a common practice, which may lead to the development of antimicrobial resistance (AMR)—a major health concern worldwide. The most common reason for the development of AMR is a lack of education and regulatory policies and the lack of community pharmacists.ObjectiveTo assess various factors that lead to self-medication with antibiotics, which might cause AMR and hinder effective healthcare.MethodsA cross-sectional study was carried out using a predesigned questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
4
12
0
1
Order By: Relevance
“…A total of 24 studies were identified and included in this scoping review study; the characteristics of the included studies are presented in Table 1 . These studies were executed using different methodologies such as cross-sectional [ 12 , 13 , 14 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], quantitative, [ 40 , 41 , 42 ] and mixed-methods or observational designs [ 23 ]. The number of participants in these studies ranged from 100 to 2696 and publication dates ranged from 2009 to 2018.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 studies were identified and included in this scoping review study; the characteristics of the included studies are presented in Table 1 . These studies were executed using different methodologies such as cross-sectional [ 12 , 13 , 14 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], quantitative, [ 40 , 41 , 42 ] and mixed-methods or observational designs [ 23 ]. The number of participants in these studies ranged from 100 to 2696 and publication dates ranged from 2009 to 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Data on attitude, prevalence, sociodemographic factors, predictors and causes of SMA were collected from self-completed questionnaires [ 13 , 14 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 37 ], face-to-face interviews [ 32 , 36 , 38 , 40 , 41 , 43 ] and observer-rated compliance with recommendations [ 23 ]. Four of the studies were undertaken in Saudi Arabia [ 28 , 29 , 30 , 39 ], three in Pakistan [ 12 , 13 , 42 ], two studies in Jordan [ 40 , 41 ] and Turkey [ 38 , 41 ] and one each from Bangladesh, [ 24 ] Bulgaria [ 23 ], Beirut, [ 32 ] Cameroon [ 33 ] Columbia, [ 34 ] Greece, [ 25 ] Guatemala, [ 35 ] Haiti, [ 36 ] Indonesia [ 26 ] Cyprus, Egypt, Lebanon, Libya, Tunisia, [ 41 ] Nigeria, [ 14 ] Poland, [ 37 ] Portugal, [ 27 ] Romania, [ 43 ] and the United Arab Emirates [ 31 ]. All studies were conducted on the lay public from differe...…”
Section: Resultsmentioning
confidence: 99%
“…The residents were predominantly low income earners with petty trading and student occupants of Kwara State College of Education, Institute of Technology of Kwara State Polytechnic and Al-Hikmah University and in this study we employed a descriptive cross-sectional design, and residents who were 18 years and above were included in the study. A sample size of 294 was calculated using Fisher's formula for a study using analytical study design with the level of confidence set at 95% and a precision of 0.05 [19].…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Surprisingly, the overall consumption of antibiotics has increased by 65% from 2000 to 2010 (Klein et al, 2018). Several causes of the irrational use of antibiotics in Pakistan include: an inadequate number of trained medical staff such as infectious disease (ID) physicians and clinical pharmacists, a lack of standard diagnostic labs, the availability of antibiotics over the counter, patients' selfmedication, poor public awareness about the use of antibiotics, and the prescribing of antibiotics by unlicensed practitioners (Gillani et al, 2017;Nazir and Azim, 2017;Hussnain, 2018;Muhammad Majid Aziz et al, 2018;Centre for Disease Dynamics, Economics and Policy, 2018b;Hayat et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%